Rancangan Aplikasi Mobile Agribis Investasi Syari’ah - Asep Yudistira Saputra; Safitri Ristanti; Sultan Rafly Sya’Ban; Sofyan Mufti Prasetiyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
With the advent of the Industrial Age 4.0, technological developments occurred in various fields, such as agriculture. Basically there are many programs that help rural workers such as iGrow, TaniFund and Tanijoy. However, farmers find it difficult to obtain the funds needed to cultivate their land, because many conditions are needed, such as: a minimum land area, joining a farmer group, or having a business entity. With that in mind, we hope to have an application that is easy to use and combines the functions of several applications into one. An example is the agribis Invest shari'ah mobile application, which is expected to be the answer. Mobile agribis invests Syari'ah can provide information about the land to be invested and other information about agriculture. With a sharia-based investment system. Sharia investment products that use sharia principles in their system use profit sharing contracts. Investments from an Islamic perspective can only be made on instruments that are in accordance with Islamic Shari'a and do not contain usury. Investments can also only be made on securities issued by parties (issuers) that do not conflict with Shari'ah. The methodology used in developing this application is research and development (R&D). The Islamic Investment agribis Mobile prototype was initially implemented in a pilot area with support. This is done so that the quality of the data entered by farmers meets the standards set.